Geochemical characteristics of the Chang7 organic-rich fine-grained sedimentary rocks and its relationship with the tight oil in Longdong area, Northwest China - Yongliang Gao (Journal of Petroleum Exploration and Production Technology, 2020)
Abstract In order to study the geochemical characteristics of fine-grained sedimentary rocks and clarify its relationship with the tight oil reservoir, the Chang7 Member of Triassic Yanchang Formation in Longdong area was taken as an example to be studied by rock pyrolysis, isotopic determination, maceral analysis, gas chromatography and gas chromatography–mass spectrometry. Lacustrine organic-rich fine-grained sedimentary rocks can be divided into organic-rich shale and organic-rich mudstone according to their lithology and texture. The results show that the organic-rich shale was deposited in a quiet and anoxic deep lacustrine environment, the organic matter was of high abundance and mainly sourced from plankton and benthic algae (type I–II1). Organic-rich mudstone mainly deposited in the semi-deep lacustrine environment, where the water was relatively shallow and the salinity was low, the organic matter was of low abundance and came from the mixed source of plankton and terrestrial clastic (type II1–II2). The Chang7 tight oil is widely distributed in the turbidite sand bodies, and it was mainly sourced from the Chang7 organic-rich shale.